Integrated early childhood development policy in Iran: a stakeholder analysis - Omolbanin Atashbahar; Ali Akbari Sari; Amirhossein Takian; Alireza Olyaeemanesh; Efat Mohamadi; Sayyed Hamed Barakati (BMC, 2021)
Abstract Background Many stakeholders are involved in the complicated process of policy making in integrated early childhood development (IECD). In other words, there are many challenges for IECD policy making in developing countries, including Iran. The aim of this study was to identify potential stakeholders and their interactions in IECD policy making in Iran. Method A mixed-methods study was conducted in two phases in 2018. First, forty semi-structured interviews and a review of IECD-related documents were conducted to identify potential stakeholders and their roles. Second, using a designed checklist, these stakeholders were assessed for power, interest, and position in IECD policy making. Then, a map of stakeholders and a three-dimensional stakeholder analysis figure were designed. Results The results of this study showed that various stakeholders, including governmental, semi-governmental, social, non-governmental and international organizations, potentially influence IECD policy in Iran. They were found to have diverse levels of power, interest and position in this regard, leading to their different impacts on the process. This diversity is assumed to have affected their levels of participation and support. Also, we found that the stakeholders with a high-power level do not have a high level of interest in, or support for, IECD policy. In general, organizational competition, complicated inter-sectoral nature of this process, insufficient budget, insufficient awareness about the importance of IECD, lack of priority given to IECD in relevant organizations, economical views rather than developmental perspectives, and lack of commitment among top managers are the reasons why this policy enjoys a low degree of support. Conclusions There are weaknesses in effective interactions and relationships among IECD policy stakeholders. This will lead to the lack of equal opportunities for optimal early childhood development. To improve this process, advocacy from high-level authorities of the organizations, negotiation with child-friendly groups, establishing a body to coordinate and oversee children's affairs, using the capacity of non-governmental organizations, strengthening inter-sectoral collaboration by clarifying the roles and responsibilities of stakeholders and the relationships between them, and increasing public awareness can be helpful.